Reformulation of Certain Circumstances Indicator as a Prerequisite for the Imposition of Death Penalty in Corruption Crime - Hidayat, Syamsul; Rodliyah; Amiruddin, Amiruddin; Parman, Lalu (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The massive practice of corruption is a serious threat to the welfare of a country so that the Indonesian government through its regulations stipulates corruption as one of the extra ordinary crimes, the seriousness of eradicating corruption is stated by regulating the death penalty for perpetrators of corruption. the implementation of the death penalty is regulated in the law on corruption, which only applies to corruptors whose actions are committed during certain circumstances. This research analyzes the indicators of certain circumstances as a prerequisite for the imposition of the death penalty in the crime of corruption. The main approaches used in this research are conceptual approach and legislative approach. The results of this study indicate that there are weaknesses in the juridical context so that there is a need for juridical reformulation related to certain circumstances indicators as a prerequisite for the imposition of death penalty sanctions in the crime of corruption.